2021
DOI: 10.1186/s12958-021-00836-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GnRH antagonist pretreatment before ovarian stimulation in a GnRH antagonist protocol in normal ovulatory women undergoing IVF/ICSI: a randomized controlled trial

Abstract: Background Synchronization of follicles is key to improving ovulation stimulation with the gonadotropin-releasing hormone (GnRH) antagonist protocol. GnRH antagonist administration in the early follicular phase can quickly decrease gonadotrophin (Gn) levels and achieve downregulation before stimulation, which may improves synchronization. A previous small randomized controlled study (RCT) showed that pretreatment with a GnRH antagonist for 3 days before stimulation may increase oocyte retrieval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The GnRH agonist long-acting protocol is one of the mainstream protocols of COS in China because of its advantages such as effectively improving endometrial receptivity and increasing the clinical pregnancy rate of fresh IVF cycles (4,5). The GnRH antagonist protocol, on the other hand, is widely used because of its shorter duration of stimulation and its association with a low incidence of ovarian hyperstimulation syndrome (OHSS) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The GnRH agonist long-acting protocol is one of the mainstream protocols of COS in China because of its advantages such as effectively improving endometrial receptivity and increasing the clinical pregnancy rate of fresh IVF cycles (4,5). The GnRH antagonist protocol, on the other hand, is widely used because of its shorter duration of stimulation and its association with a low incidence of ovarian hyperstimulation syndrome (OHSS) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial (RCT) involving 69 patients by Blockeel C [12] also showed that 3-day antagonist pretreatment followed by ovulation stimulation during menstruation increased the number of retrieved oocytes but did not improve the rate of ongoing pregnancy. Our team's RCT research [4] showed an increased sample size but found no improvement in the number of retrieved oocytes or the pregnancy rate in regular ovarian responders.…”
Section: Discussionmentioning
confidence: 86%
“…Protocols [4] In the conventional antagonist protocol (control group), ovarian stimulation with Gn was initiated on day 2 of the menstrual cycle (C2). In the pretreatment GnRH-ant protocol (study group), ovarian stimulation was performed after three days (C5) of GnRH-ant pretreatment (Cetrotide®, 0.25 mg cetrorelix acetate, Serono, Inc.).…”
Section: Inclusion Criteria and Exclusion Criteriamentioning
confidence: 99%
“…GnRH antagonist administration in the early follicular phase can decrease gonadotrophin levels, which may improve synchronization of follicles, improving ovulation stimulation (50). Maged et al in 2015 compared a delayed start protocol with a standard protocol that used a gonadotropin releasing hormone antagonist (GnRH antagonist) in poor responding patients (51).…”
Section: Gonadotropin Releasing Hormone (Gnrh)mentioning
confidence: 99%